Methodology for Assessment the Possibility of Transfer Six-Phase Power Line into the Mode of Operation with Incomplete Number of Phases - Kiorsak M.V.; Turturica N.N. (Problems of the Regional Energetics, 2020)
In electric power systems due to various reasons: short circuits, phase breaks, ice melting, phase-by-stage repair of a high-voltage power line (transmission line), interruptions in the power sup-ply to the consumer occur. On single-sided power lines, this leads to a prolonged shutdown of consumers, and to a significant emergency lack of electricity supply. Switching the line to opera-tion with incomplete number of phases significantly increases the reliability of consumes power supply. For double-circuit power lines it is always possible to keep in work at least two phases out of six. Among the various options for double-circuit power lines, the so-called self-compensating and controlled self-compensating high-capacity power transmission lines (SCL and CSCL) were proposed. For unidirectional power supply lines, these cases are accompanied by a prolonged shutdown of consumers from the electrical energy and a long time with a lack of supply. The article is devoted to the methodology for calculation the throughput of SCL and CSCL, which operate with incomplete number of phases. The methodology is based on the use of six symmetric components of currents and voltage of the SСL (СSС) and can be extended and applied in principle to any six-phase power transmission lines, in particular, two-circuit con-ventional power lines. The equivalents substitution complex schemes in the coordinates of the six symmetrical components in the MATLAB program are modeled. This allows us to find the currents and transmitted power through the line and voltages in the nodes of the network and evaluate the possibility of its operation in this mode.